THE ROLE OF NUTRITION IN THE PREVENTION OF TRANSIENT RESPIRATORY INFECTIONS AMONG MILITARY PERSONNEL (World Bulletin of Public Health, 2026)
The article presents an analytical overview of modern scientific research dedicated to the issues of spread and prevention of transient (acute) respiratory infections among military personnel in various countries. The epidemiological features of respiratory tract infections in the military environment, as well as risk factors including crowded living conditions, intensive physical exertion, psychoemotional stress, climatic conditions, and nutritional status, are considered. The results of randomized clinical trials and systematic reviews devoted to the role of vitamins C and D, zinc, probiotics, and energy sufficiency of the diet in the prevention of upper respiratory tract infections are analyzed. It is shown that correcting micronutrient deficiencies and ensuring adequate energy balance help to reduce the frequency and severity of acute respiratory infections in the context of military service.
Keywords: military personnel; acute respiratory infections; immunity